Highly Efficient Organic Solar Cells Consisting of Double Bulk Heterojunction Layers. Issue 19 (15th March 2017) - Huang, Jiang; Wang, Hanyu; Yan, Kangrong; Zhang, Xiaohua; Chen, Hongzheng; Li, Chang‐Zhi; Yu, Junsheng
Abstract : An organic solar cell (OSCs) containing double bulk heterojunction (BHJ) layers, namely, double‐BHJ OSCs is constructed via stamp transferring of low bandgap BHJ atop of mediate bandgap active layers. Such devices allow a large gain in photocurrent to be obtained due to enhanced photoharvest, without suffering much from the fill factor drop usually seen in thick‐layer‐based devices. Overall, double‐BHJ OSC with optimal ≈50 nm near‐infrared PDPP3T:PC71 BM layer atop of ≈200 nm PTB7‐Th:PC71 BM BHJ results in high power conversion efficiencies over 12%. Abstract : An organic solar cell (OSCs) containing double bulk heterojunction (BHJ) layers, namely, double‐BHJ OSCs is constructed via stamp‐transferring of low bandgap BHJ layer atop of mediate bandgap active layers. Such devices obtain a large gain in photocurrent due to the enhanced photo harvest with little fill‐factor drop. Overall, double‐BHJ OSC results in high power conversion efficiencies over 12%.